Irish Empire: assembling the geographical imagination of Irish missionaries in Africa. (July 2014) - Linehan, Denis
Throughout the 20th century the books, exhibitions, public lectures, magazines, film and television shows produced by Irish missionaries created a vivid portrayal of Africa within Ireland. Until recently, so clearly were these missionary enterprises associated with an idea of Ireland as a champion of the Global South that their history and their rich visual and material culture existed beyond critique. This paper will contest this established national narrative, through an excavation of the geographical culture of Irish Catholic missionaries and their depictions of Africa between 1900 and 1940, when many of the principal imaginaries about the continent and its peoples were lodged in the Irish consciousness. To undertake this analysis, this paper will deploy concepts of assemblage rather than colonial discourse analysis, the method that has more frequently been used to consider the geographical imaginaries associated with the visual and material culture that intersects with colonialism. This proposition is derived from the contention that in presenting a fluid but materialized vision of society, attendant to the turbulent qualities of social, spatial and non-human relationships, assemblage creates illuminating opportunities to trace how knowledges about Africa were continuously transacted through the Irish missionary enterprise – in bodies, books, the built environment and so on, as well as through the immanent qualities of the missionary network itself. Assemblage offers the potential to re-situate 'the geographical' within missionary activities, by recognizing their dependency upon the circulation of information, materials and personnel over a wide network and through multiple modes of encounter and knowledge making. In this way, the paper contributes to the recasting of geography's history, though an exploration of the relationships between geographical practices and the contexts, practices and networks in which they have been situated. Equally, examination of the early 20th-century Catholic missionary enterprise offers critical insights into the complexities and dramas of Irishness in the context of Empire.